2019
DOI: 10.1051/ro/2018094
|View full text |Cite
|
Sign up to set email alerts
|

Governmental subsidy policies and supply chain decisions with carbon emission limit and consumer’s environmental awareness

Abstract: The carbon emission reduction has become an inevitable trend. Under the low-carbon environment, the government has been acting as an important role in the operation and management of supply chain. This paper considers four different governmental subsidy strategies, which includes none of members is subsidized (NS Scenario), only retailer is subsidized (RS Scenario), only manufacturer is subsidized (MS Scenario) and both members are subsidized (SS Scenario). A Stackelberg game model, which incorporates both gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…erefore, the larger the competition intensity is, the more fierce the collection is. Consistent with Zou et al [48], Xu et al [49] and Jerbia et al [50], we get a symmetric influence between two channels. We suppose there exists competition between the two collection channels.…”
Section: Assumptionsupporting
confidence: 92%
“…erefore, the larger the competition intensity is, the more fierce the collection is. Consistent with Zou et al [48], Xu et al [49] and Jerbia et al [50], we get a symmetric influence between two channels. We suppose there exists competition between the two collection channels.…”
Section: Assumptionsupporting
confidence: 92%
“…Besides these, many of the researchers have worked in these directions in recent trends [8,23,31]. From the Table 1, it can be concluded that this study is partially similar to Ranjan and Jha [20] and Mondal et al [18].…”
Section: Promotional Effortsupporting
confidence: 71%
“…When discussing carbon trading, the extant literature assumes that the carbon price is a fixed exogenous variable [40][41][42][43]. However, we assumed that the carbon price is affected by Demand and Supply and found that with the increase in the carbon price sensitivity coefficient, the e-commerce platform's sales promotion service first increases and then declines, and the manufacturer's profit first declines and then increases.…”
Section: Resultsmentioning
confidence: 89%